Islamic Leadership Management in the Development of a Religious School Culture - Topan Iskandar; Muhammad Thalal; Wulan Sari; M. Fadli Al Azhari (MASI Mandiri Edukasi, 2026)
Education plays a strategic role in shaping students' religious character, making the development of a religious school culture an essential necessity in addressing the challenges of moral degradation in the era of globalization. This study aims to analyze Islamic leadership management in the development of a religious school culture in several schools in Indonesia. The study uses a qualitative approach with a multisite study design. Data were collected through in-depth interviews, participatory observation, and document studies involving principals, teachers, education staff, and students as informants. Data analysis was conducted thematically using an interactive analysis model that includes data reduction, data presentation, and conclusion drawing, and its validity was tested through triangulation and member checking. The research results indicate that Islamic leadership management is applied systematically and continuously through the functions of planning, organizing, implementing, and evaluating school programs. The principal plays a central role not only as an administrative manager but also as a moral and spiritual exemplar in fostering the internalization of Islamic values. The development of a religious school culture is realized through the habituation of worship, the integration of religious values into the learning process, and the formation of students' and school members' morals and ethics. The research findings confirm that Islamic leadership that is trustworthy, participative, and consistent can build a religious school culture that is tangibly internalized in school life and contributes to the holistic character formation of students.